Pragmatisme Hukum dan Sunset Review: Menuju Proses Legislasi yang Responsif dan Akuntabel - Xavier Nugraha; Jeniffer Avrillya Wibisono; Gwyneth Eugenia Keisya Howard; Angelica Novia Walasondakh (Jurnal Hukum Lex Generalis, 2025)
Indonesian legislation is frequently enacted in disregard of essential foundation, rendering the legislative process merely formalistic. This results in compromised quality and a lack of systematic evaluation regarding regulatory effectiveness, contradicting legal pragmatism which prioritizes practical utility and social impact. To bridge this gap, implementing a Sunset Review mechanism is highly necessary in Indonesia. This mechanism mandates the legislature to periodically review regulations within a spesific timeframe to determine their continued validity. Consequently, this ensures that Indonesia’s legal instruments remain responsive, accountable, and adaptive to societal dynamics.